The Impact of AI Adoption on Job Engagement and Employee Trust - Adityaksa, Rezha; Suyoso, Aldo Lovely Arief (Manunggal Halim Jaya, 2025)
The adoption of Artificial Intelligence (AI) within organizations has introduced several phenomena impacting employee motivation. One significant area of interest is the perception of AI principles among employees Employees' views on the effectiveness of AI principles in their organization can vary greatly depending on their roles and responsibilities. For example, a junior data scientist might perceive the principles differently than a Chief Analytics Officer due to their varying levels of involvement and understanding of AI's strategic implementation. This research aims to examine the influence of AI Adoption in moderating job engagement on employee trust compared to the direct influence of job engagement on employee trust. Quantitative research method using non-probability sampling and purposive sampling technique method of 200 mass media employees in Surabaya. Data analysis techniques using Smart PLS software with hypothesis testing using PLS-based SEM. The research results show that AI Adoption is able to moderate the influence of job engagement on employee trust and there is a direct influence of job engagement on employee trust.